Anmeldelser - Kremer, Joachim (Danish Yearbook of Musicology, 1997)
Review of: Niels W. Gade. Works I:4. Symphony no. 4 op. 20, red. af Niels Bo Foltmann. Foundation for the Publication of the Works of Niels W. Gade, København 1995. (Distribution Engstrøm og Sødring / Bärenreiter Verlag). Niels W. Gade. Works II:1. Octet, Sextet and Quintets for strings, red. af Finn Egeland Hansen. Foundation for the Publication of the Works of Niels W. Gade, København 1995.